A trajetória e a funcionalidade da universidade pública brasileira - Júnia Maria Zandonade Falqueto; Josivania Silva Farias (Revista Gestão Universitária na América Latina, 2013)
This paper aims at a reflection on the management model of the Brazilian federal universities. The main objective is to analyze the influence of two important models of public administration (bureaucracy and managerialism) on university management in the country. Initially, the history of the university in Latin America is brought under appreciation, emphasizing the history of Brazil. Next the influence of the bureaucratic model will come under close scrutiny. Finally, this paper addresses the managerial logic as regards Brazilian higher education, assuming it is a new paradigm to the university management. It starts with a theoretical apparatus that subsidizes the development of critical thinking about the trajectory and functionality of these institutions. The results show that Brazilian universities are managed from bureaucratic structures, leading to a scenario which proves low-achieving and conducive to conflicts in decision making, although the literature and the daily life of these organizations alike already mirror the managerialist discourse which assumes the adjustment of universities to the logic of management as viewed in the private sector. There is no advocating here that public universities should be veered into the privatization-minded logic of the public, good and free, nor deprived of their autonomy. However, it might prove salutary to rethink the struggle against such characteristics harmful to the management of them as corporatism, the excess of rules and rigidity.